2002
DOI: 10.1088/0031-9155/47/5/311
|View full text |Cite
|
Sign up to set email alerts
|

Speed of particles ejected from animal skin by CO2laser pulses, measured by laser Doppler velocimetry

Abstract: During ablation of tissue with laser pulses rapid sublimation of matter occurs and high pressures are exerted within the tissue, resulting in steam. smoke and particles being expelled. In this paper we report the speed of particles ejected from animal tissue exposed to CO2 laser pulses measured directly by laser Doppler velocimetry (LDV). Speeds recorded just above animal skin were in the range of 9 to 18 m s(-1) for laser pulses of 128 to 384 J cm(-2) respectively. Aerodynamic turbulence slowed the particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The results of a 2002 study by Nicola et al 34 helped explain how all surgical team members could be exposed to similar levels of surgical smoke. They measured the speed and distance that smoke particles were ejected from lasered animal skin.…”
Section: Efforts To Raise Awarenessmentioning
confidence: 99%
“…The results of a 2002 study by Nicola et al 34 helped explain how all surgical team members could be exposed to similar levels of surgical smoke. They measured the speed and distance that smoke particles were ejected from lasered animal skin.…”
Section: Efforts To Raise Awarenessmentioning
confidence: 99%
“…The smaller the particle size, the further it can travel. Studies have shown that not just the members of the operating team standing in close proximity to generation of smoke (the surgeons performing the procedure, scrubbed nurse) but members who are at a distance from the operating table like the circulating nurse, technicians, anesthesiology team members are also affected [15]. Particles larger than 100 μm remain airborne, those 5 μm of larger get deposited in the larger airways (wall of the nose, larynx, trachea and large bronchi) while those 2 μm or smaller reach the bronchioles and alveoli and get deposited there [16,17].…”
Section: Electrosurgery and Surgical Smokementioning
confidence: 99%
“…Concern about respiratory exposure is warranted. Nicola et al (2002) measured the speed of particles released during CO 2 laser surgery and reported that laser ablation sends particles approximately 1 meter above the ablation origin (i.e., approximately face height).…”
Section: Research On the Risk Of Exposure To Surgical Smokementioning
confidence: 99%
“…Bovine HPV was found in the surgical smoke and tumours developed in the skin of reinoculated calves Nicola, et al 2002 The speed of particles in surgical smoke was recorded from animal tissue exposed to CO2 laser.…”
Section: Cautery Co2 Lasermentioning
confidence: 99%